Comprehensive Evaluation of Clinical Application of Balanced Compound Amino Acid Injection - Shi, Yingqin; Song, Hai; Liu, Jinyan; Lin, Jie; Fang, Lingzhi (Frontiers in Nutrition, 2022)
Background: To provide a reference for hospital drug selection and rational clinical drug selection based on evaluation of the safety, nutritional quality and economy of 27 manufacturers of five varieties (18AA, 18AA-I, 18AA-II, 18AA-IV, 18AA-V) of balanced compound amino acids for injection and (18AA-IIoriginal research). Methods: The safety of compound amino acids for injection was evaluated by comparison of antioxidant sulfite contents. Based on the amino acid scoring standard mode and the whole egg protein mode proposed by the Food and Agriculture Organization of the United Nations /World Health Organization (FAO/WHO) in 1973, we compared the formula, the first limiting amino acid content and the comprehensive quality of the total essential amino acid (EAA) contents of the six formulations were studied. The price/content ratio was used to evaluate their economy. Results: The same variety produced by different manufactures had the same formula and contents of balanced compound amino acids for injection. Safety: 18AA-IIoriginal research and 18AA-II had the lowest sulfite content. Compared with 18AA-IIoriginal research， the sulfite content of 18AA-I, 18AA, 18AA-V and 18AA-IV were higher (10 times, 16.67 times, 16.67 times and 33.33 times, respectively). The lower the sulfite content, the safer the product. Nutritional quality: The proportions of amino acids in the five varieties of compound amino acid injection were all suitable. The order of the first limiting amino acids for the formulations was 18AA-IIoriginal research = 18AA-II＞18AA ＞18AA-I = 18AA-IV＞18AA-V. The order of the EAA values for the formulations was 18AA-IIoriginal research = 18AA-II＞18AA＞18AA-I >18AA-IV>18AA-V. The overall effectiveness order was 18AA-IIoriginal research = 18AA-II＞18AA > 18AA-I＞18AA-IV＞18AA-V. Economy: Among the 27 manufacturers, 12 manufacturers had a price/content ratio higher than that of 18AA-II original research manufacturers, 15 manufacturers had a price/content ratio lower than original research manufacturers. Conclusion: Through its security, effectiveness, economy of the comprehensive research, we recommended 18AA-II and 18AA-IIoriginal research with high safety, efficacy and reasonable price as the first choice. 18AA and 18AA-I with better safety and reasonable price, secondary recommendation. 18AA-IV or 18AA-V with poor safety, efficacy and economy, not recommended.